The state's role of digital economy and economic innovation in Vietnam - Trung, Phan Nhan (PT. Riset Press International, 2024)
This study investigates the role of the Vietnamese government in fostering the digital economy and economic innovation. Utilizing linear regression analysis through SPSS, the research analyzes data from various reliable sources to examine the intricate relationship between digital economy advancements and economic innovation trends, highlighting the mutual reinforcement between these factors. Key findings indicate that the government’s involvement in establishing digital infrastructure, developing human resources, and creating supportive legal frameworks has significantly impacted the development of the digital economy. The integration of new technologies such as AI, IoT, and blockchain is pivotal, not only for generating new products and services but also for enhancing existing business processes, thereby driving digital economic growth. Human resources are crucial, necessitating government policies that facilitate continuous skill updates and support workforce adaptation to technological changes. Furthermore, government policies promoting business innovation through financial support and tax incentives are essential for maintaining competitiveness and economic development. Digital transformation, supported by robust ICT infrastructure and legal frameworks, is becoming an inevitable trend with profound impacts across various sectors. Environmental considerations and social welfare in the context of Industry 4.0 are also critical, requiring policies that balance technological advancements with sustainable practices and labor market adaptations. The study concludes that the Vietnamese government plays a vital role in shaping a conducive environment for the digital economy and economic innovation, emphasizing the importance of collaborative efforts between public and private sectors. These findings underscore the need for continued investment in digital infrastructure, education, and supportive policies to maximize societal and economic benefits.